(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Background: Chronic Osteomyelitis is a debilitated disease and is characterized by persistent and prolonged infection of the bone and its management remained an increasing challenge to clinicians due to growing resistances to antibiotics. Objective: The proposed study was conducted to ascertain the antibiotic sensitivity pattern of bacterial isolates in chronic osteomyelitis patients. Materials and methods: This descriptive study was conducted for a period of six months from June to November 2021. A total of 80 samples of pus and other exudates were collected from all the patients ≥ 18 years of age with either gender and diagnosed with chronic osteomyelitis˃6 weeks duration. The samples were sent for microbiological examination and culture. Various organisms were identified by standard methods. Antibiotic sensitivity pattern of detected microorganisms was also analysed. Patients with other form of arthritis, implant related osteomyelitis and who had antibiotic usage in last one week were excluded from our study. Results: Out of 80 patients, 73 (91%) showed growth of microorganisms whereas remaining 7 (9%) samples were sterile. The commonest bone affected in the study was tibia 53 (66.3%). Staphylococcus aureus was the most common bacteria isolated in 57 (78%) of patients. Maximum antibiotic sensitivity pattern was noted for vancomycin and clindamycin ( ˃90%) while maximum resistance was noted for penicillin in 22 (31%) of patients. Conclusion: Our study will thereby guide the clinicians in choosing appropriate antibiotics which not only contribute to better treatment but the judicious use of such antibiotics will also help in preventing emergence of resistance to drugs, which are still sensitive.